Reproductive biology of the guitarfish Rhinobatos percellens (Chondrichthyes, Rhinobatidae) from the São Paulo Coast, Brazil, western South Atlantic Ocean - Rocha, F. [UNESP]; Gadig, O. B F [UNESP] (Wiley, 2013)
The reproductive biology of the guitarfish Rhinobatos percellens was studied from 751 specimens caught by bottom pair trawlers off the coast of São Paulo, Brazil, between c. 24° 00′ S; 45° 15′ W and c. 25° 10′ S; 47° 52′ W, from September 2007 to August 2009. The total length (LT) and total mass (MT) relationship for males and females combined was MT = 1·29E-06 LT 3·15 (r = 0·99, n = 751). The mean LT of sexually mature specimens was 548 mm for males and 583 mm for females. Clasper growth was allometric and showed three distinct phases. Most claspers were calcified in specimens of c. 550 mm LT. The mean diameter of the largest oocyte was 29·8 mm, the mean ovarian fecundity was seven oocytes and ovulation occurred between August and November. Uterine fecundity ranged from two to 13 embryos (mean of five embryos). Larger females had higher litter sizes and larger embryos; the size-at-birth was c. 200 mm LT. The hepato-somatic index oscillated seasonally for males and females; the gonado-somatic index had little variation in males, but varied seasonally in females. The presence of many non-pregnant adult females and of encapsulated eggs during two consecutive seasons suggests a resting period between gestations and the possibility of diapause. © 2012 The Authors. Journal of Fish Biology © 2012 The Fisheries Society of the British Isles.
Keywords: Ovaries; Reproduction; Sexual development; Testes; animal; animal embryo; Atlantic Ocean; body size; Brazil; cytology; female; fertility; histology; male; oocyte; physiology; reproduction; season; skates (fish); Animals; Body Size; Embryo, Nonmammalian; Female; Fertility; Male; Oocytes; Seasons; Skates (Fish); Chondrichthyes; Rhinobatidae; Rhinobatos percellens